Analisis Fiqh Mawaris Islam: Status Janin sebagai Ahli Waris dan Kasus Kematian Massal (al-Halāk al-‘Ām) - Aldi .; Abd Ghafur (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
culinary businesses, with a specific focus on Angkringan Sendang 86 in Kraksaan. Using a qualitative research method with a literature review approach, this study examines a variety of scientific sources published between 2020 and 2024 that discuss service quality, customer comfort, consumer behavior, and customer loyalty in the micro-culinary sector. The findings indicate that service quality which includes friendliness, service speed, cleanliness, accuracy of presentation, and professionalism significantly affects customers’ perceptions and levels of satisfaction. Additionally, comfort factors such as physical environment, spatial layout, ambiance, and supporting facilities play an essential role in shaping positive customer experiences. The literature further emphasizes that the combination of optimal service quality and adequate comfort can enhance customer loyalty and attract new visitors through word-of-mouth recommendations. Therefore, strengthening both aspects is crucial for angkringan business managers to remain competitive and sustainable in an increasingly competitive culinary landscape.